2019
DOI: 10.1111/cea.13465
|View full text |Cite
|
Sign up to set email alerts
|

Blood eosinophil count correlates with severity of respiratory failure in life‐threatening asthma and predicts risk of subsequent exacerbations

Abstract: Background An elevated blood eosinophil count when asthma is stable predicts exacerbations and therapeutic response to corticosteroids or biologics targeting eosinophils. Few studies have examined the prognostic value of blood eosinophils measured at exacerbation. Aim To elucidate the relationship between a spot blood eosinophil count–measured at the onset of a life‐threatening asthma exacerbation–with indices of exacerbation severity and risk of subsequent exacerbations. Methods Real‐world, retrospective revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…This represents a critical gap in asthma care to be urgently addressed via better implementation of quality asthma care. Failure to provide ICS controller medication and follow-up assessment have been consistently cited as avoidable factors in national audits of patients with fatal or near-fatal asthma in Singapore 36 and internationally, 37 38 and our study has shown that it is possible to address them with extended availability of specialist asthma nurse counselling after-hours.…”
Section: Open Accessmentioning
confidence: 72%
“…This represents a critical gap in asthma care to be urgently addressed via better implementation of quality asthma care. Failure to provide ICS controller medication and follow-up assessment have been consistently cited as avoidable factors in national audits of patients with fatal or near-fatal asthma in Singapore 36 and internationally, 37 38 and our study has shown that it is possible to address them with extended availability of specialist asthma nurse counselling after-hours.…”
Section: Open Accessmentioning
confidence: 72%
“…53 Although a retrospective review, the study by Yii and colleagues related blood eosinophils on admission during a life-threatening asthma attack, to clinical parameters such as arterial blood gases and duration of mechanical ventilation. 54 The acute blood eosinophil count on admission did not relate to outcome for the acute admission. However, an admission eosinophil count of A biomarker that is now part of diagnostic guidelines for asthma in both children and adults is an elevated exhaled nitric oxide (FeNO) level.…”
Section: Biomarkers and Mechanisms Of Diseasementioning
confidence: 90%
“…Blood eosinophil count >115 cells/mm 3 were significantly though weakly correlated with a T2-high signature (38). Despite being a poor biomarker in determining asthma phenotype, high blood eosinophil counts (>1,200 cells/mm 3 ) were recently associated with a higher risk of recurrent exacerbations in patients admitted to the ICU for near-fatal asthma (39).…”
Section: Phenotyping According To Granulocyte Bronchial Infiltrationmentioning
confidence: 99%